Response mechanism of major secondary metabolites of Polygonatum kingianum to selenium nanoparticles - Wan, Xiaolin; Wang, Jiehua; Zhang, Jiaxin; Cui, Hongshi; Cui, Lingjun; Xiao, Qiang (Frontiers in Plant Science, 2024)
Selenium nanoparticles (SeNPs) can be absorbed by plants, thereby affecting plant physiological activity, regulating gene expression, and altering metabolite content. However, the molecular mechanisms by which exogenous selenium affects Polygonatum kingianum coll.et Hemsl plant secondary metabolites remain unclear. In this study, we exposed P. kingianum plants to SeNPs at 0, 10, 25, and 50 mg/L concentrations. Joint physiological, metabolomic, and transcriptomic analyses were performed to reveal the response mechanisms of major secondary metabolites of P. kingianum to SeNPs. Our data shows that under the treatment of 25 mg/L, the photosynthetic electron transfer rate of plants significantly increases and the carbon-nitrogen ratio significantly decreases. In parallel, the main active components, polysaccharides and saponins, showed a significant increase in content, while flavonoid content decreased. SeNPs affect polysaccharide accumulation mainly through up-regulation of SPS, UGPase, AGPase, UTP, and SUS genes in starch and sucrose metabolic pathways. The accumulation of saponins was affected by upregulating genes in the sesquiterpenoid and triterpenoid biosynthesis pathways, including PAD, ADH, PK, and GS. The accumulation of flavonoids was mainly regulated by metabolic pathways such as flavonoid biosynthesis, isoflavonoid biosynthesis, and the biosynthesis of phenylpropanoids. In summary, this study reveals the key metabolic pathways affected by SeNPs in the main secondary metabolic products of P. kingianum.